Design And Analysis Of Rubber Tapping Machine Using Ansys Software - Chong, Zhi Chien (Universiti Sains Malaysia, 2021)
Rubber products are important and took up few percentages of Malaysia’s total exports. Due to this, it is necessary to improve the quantity of natural rubber that been produced. However, the number of skilled rubber tappers are getting lower nowadays, and the available manual tools are unable to cope with the high demand of variable products to be produced. In this study, a new design of Rubber Tapping Machine (RTM) is introduced as a solution to this problem. The designed semi-automatic RTM with rotational cutting tool can complete the tapping process in 16 s of time. This tool involved a minimum labour contact, where in they just need to move the cutting tool or the tapping head down by pressing switch until the cutting tool contacted with the previous tapping wound. Then, execution button is used to carry out the whole tapping process. By using ANSYS software, the modal, frequency response, transient and stress analyses are conducted to analyze the performance of the RTM. Compared to the available RTM in the market, this newly designed RTM has an advantage such as convenient to be used. Also, the total estimation cost to build the RTM is considered low compared to the price of other RTMs in the market.